1992
DOI: 10.1016/s0022-5347(17)37520-1
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Citrate Absorption in Nephrolithiasis

Abstract: Gastrointestinal absorption of citrate was measured in stone patients with idiopathic hypocitraturia to determine if citrate malabsorption could account for low urinary citrate. Citrate absorption was measured directly from recovery of orally administered potassium citrate (40 mEq.) in the intestinal lavage fluid, using an intestinal washout technique. In 7 stone patients citrate absorption, serum citrate levels, peak citrate concentration in serum and area under the curve were not significantly different from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 13 publications
3
16
0
1
Order By: Relevance
“…The mechanism by which K-cit reduces urinary calcium is almost certainly multifactorial. While citrate itself is readily absorbed in the intestine, 52 it decreases calcium absorption and urinary calcium excretion. 14,15 Increased urinary citrate would also bind urinary calcium, removing the calcium from the pool available for binding with phosphate or oxalate.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which K-cit reduces urinary calcium is almost certainly multifactorial. While citrate itself is readily absorbed in the intestine, 52 it decreases calcium absorption and urinary calcium excretion. 14,15 Increased urinary citrate would also bind urinary calcium, removing the calcium from the pool available for binding with phosphate or oxalate.…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanisms of hypocitraturia include an intrinsic renal defect (dysfunction of the Na-citrate cotransporter or disordered intracellular citrate regulation), an abnormal intestinal citrate or alkali absorption, or a normal physiologic response to a high acid-ash diet [25]. However, recent controlled studies on hypocitraturic cases have concluded that the low urine citrate in stone formers was not due to an abnormality in intestinal citrate absorption, but was probably due to a diet high in animal proteins or low in fruits and vegetables [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Citrate absorption from nutritional sources in the small intestine seems to be mediated mainly via NaDC1 and NaDC3 [64, 65]. By this mechanism, more than 90% of an oral citrate load can be absorbed and hypocitraturia can be ameliorated [64, 66].…”
Section: Regulation Of Citrate Homeostasis By Slc13 Membersmentioning
confidence: 99%
“…Citrate absorption from nutritional sources in the small intestine seems to be mediated mainly via NaDC1 and NaDC3 [64, 65]. By this mechanism, more than 90% of an oral citrate load can be absorbed and hypocitraturia can be ameliorated [64, 66]. At physiological pH, most of serum citrate circulates in the form of triply charged citrate bound to divalent ions, such as calcium and magnesium, and is filtered freely at the glomerulus; reabsorption takes place predominantly in the proximal tubule via NaDC1 [65].…”
Section: Regulation Of Citrate Homeostasis By Slc13 Membersmentioning
confidence: 99%